Political changeover: «Greek» culture and education - Λαμπρόπουλος, Κωνσταντίνος (The Greek Review of Social Research, 2013)
Historically, the modern Greek community expressed itself in a polarised manner: serving emotionally impregnated ideas. The period after the fall of the colonels’ regime in 1974 followed the same historical path. By shifting the polarisation onto the field of the defence of people’s interests it led to the reconstruction of a flawed and contradictory collective ideal. However, the continuation of the same collective attitude discloses deeper cultural causes and obsessions. More specifically this attitude has been reflected in the area of education. The Greek educational system has remained divided between the self-referential and dogmatic teaching of the Greek consciousness on one hand and the teaching of an exogenous modern spirit as far as technology and economic life are concerned on the other.